Improving Open High School Teachers' Learning Activity Places Management Skills through LAP Managerial Training - Somantri, Ade; Nurhayati, Sri; Ansori, Ansori; Boriboon, Gumpanat (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2024)
Indonesia, a nation rich in natural resources, faces challenges in providing equitable access to education, particularly for children in remote areas. Open High Schools offer an alternative platform for students facing limitations in accessing regular schools. In West Java, the Open High School program aims to improve education participation rates. However, effective management of Learning Activity Places (LAPs) remains a crucial aspect of ensuring a conducive learning environment. This research investigates the urgency of LAP managerial training for Open High School teachers to enhance their LAP management skills. A phenomenological qualitative approach was used, and data was collected through interviews, observations, and documentation. The training program was well-planned, employing the andragogy approach, and focused on managerial aspects, including teamwork, module development, and LAP challenges. The evaluation showed improved LAP management skills, but some areas for improvement were identified.